A lipid transfer protein variant with a mutant eight-cysteine motif causes photoperiod- and thermo-sensitive dwarfism in rice. (8th November 2019) - Deng, Wenjun; Li, Riqing; Xu, Yiwei; Mao, Runyuan; Chen, Shuifu; Chen, Libin; Chen, Letian; Liu, Yao-Guang; Chen, Yuanling
Abstract : A gain-of-function rice mutant Photoperiod-thermo-sensitive dwarfism 1  is caused by a mutated gene,   Ptd1, that encodes a nsLTP variant with an altered protein conformation due to disruption of the conserved eight-cysteine-motif. Abstract: Plant height is an important trait for architecture patterning and crop yield improvement. Although the pathways involving gibberellins and brassinosteroids have been well studied, there are still many gaps in our knowledge of the networks that control plant height. In this study, we determined that a dominant photoperiod- and thermo-sensitive dwarf mutant is caused by the active role of a mutated gene Photoperiod-thermo-sensitive dwarfism 1 ( Ptd1 ), the wild-type of which encodes a non-specific lipid transfer protein (nsLTP). Ptd1 plants showed severe dwarfism under long-day and low-temperature conditions, but grew almost normal under short-day and high-temperature conditions. These phenotypic variations were associated with Ptd1 mRNA levels and accumulation of the corresponding protein. Furthermore, we found that the growth inhibition in Ptd1 may result from the particular protein conformation of Ptd1 due to loss of two disulfide bonds in the eight-cysteine motif (8-CM) that is conserved among nsLTPs. These results contribute to our understanding of the novel function of disulfide bonds in the 8-CM, and provide a potential new strategy for regulation of cell development and plant height by modifying the amino acid residues involved in protein conformation patterning.